2022
DOI: 10.1021/acs.estlett.1c00911
|View full text |Cite
|
Sign up to set email alerts
|

Microfibers Released into the Air from a Household Tumble Dryer

Abstract: Microfibers of polyester and cotton might be significant for the transport and fate of chemical pollutants in the air due to the amounts emitted, as well as their capacities to sorb inorganic and organic compounds. It was hypothesized that household tumble driers could be atmospheric sources of these microfibers. This study quantified the number of the two most common textile fibers discharged from a household vented tumble dryer to ambient air. The results suggest that driers of this type are a potential sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…However, these were focused on fiber collection by the lint filter, and it was not clear whether they used a vented or condenser dryer as the specific dryer model number was not given, only that it was from the Bosch Series 4 range of appliances which includes both types of dryer. A very recent report [ 26 ] concluded that tumble dryers release 433,128–561,810 microfibers to air during 15 minutes of use corresponding to an annual release of between 9 x 10 7 to 12 x 10 7 microfibers from an average Canadian household. This was reported to be greater than the quantity of fibers released by washing machines, although no actual comparison is made with the same fabric load.…”
Section: Introductionmentioning
confidence: 99%
“…However, these were focused on fiber collection by the lint filter, and it was not clear whether they used a vented or condenser dryer as the specific dryer model number was not given, only that it was from the Bosch Series 4 range of appliances which includes both types of dryer. A very recent report [ 26 ] concluded that tumble dryers release 433,128–561,810 microfibers to air during 15 minutes of use corresponding to an annual release of between 9 x 10 7 to 12 x 10 7 microfibers from an average Canadian household. This was reported to be greater than the quantity of fibers released by washing machines, although no actual comparison is made with the same fabric load.…”
Section: Introductionmentioning
confidence: 99%
“…From an analytical point of view, Hidalgo-Ruz et al [99] suggested differentiating MPs of 500 μm-5 mm and < 500 μm since the first fraction is suitable for visual sorting and spectroscopic techniques are required to differentiate the second category. Numerous studies have demonstrated the ubiquitous presence of the two size fractions of microplastics in the environment, including water [100], soil [60] and air [101]. The measurement of MPs with different size ranges has also been summarized by a series of review articles [102].…”
Section: Sizesmentioning
confidence: 99%
“…The drying process is another important source of MFs release (Kapp and Miller 2020 ). A household tumble dryer could release 433,128 (cotton) and 561,810 (polyester) microfibers in 15 min; the annual release of microfibers by a dryer may be even greater than the number of microfibers released through washing (Tao et al 2022 ). Although many literatures reported the release of MFs to the air, little attention has been paid to the additives on MFs.…”
Section: Release Of Additives From (Micro)plastic Fibersmentioning
confidence: 99%